To calculate the distance between the points \((-58, 13)\) and \((-58, 2)\), we can use the distance formula, which is:
\[ d = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \]
For the points \((-58, 13)\) and \((-58, 2)\):
- \(x_1 = -58\), \(y_1 = 13\)
- \(x_2 = -58\), \(y_2 = 2\)
Now we can substitute these values into the formula:
\[ d = \sqrt{((-58) - (-58))^2 + (2 - 13)^2} \] \[ d = \sqrt{(0)^2 + (-11)^2} \] \[ d = \sqrt{0 + 121} \] \[ d = \sqrt{121} \] \[ d = 11 \]
Thus, the distance between the points \((-58, 13)\) and \((-58, 2)\) is \(11\) units.